TOBAMOVIRUS SPECIFIC PRIMERS REVEALED A CO-INFECTION OF TOBACCO MOSAIC VIRUS AND PEPPER MILD MOTTLE VIRUS ON TOMATO IN IRAQ : TOBAMOVIRUS SPECIFIC PRIMERS REVEALED A CO-INFECTION OF TOBACCO MOSAIC VIRUS AND PEPPER MILD MOTTLE VIRUS ON TOMATO IN IRAQ (Iraqi Journal of Market Research and Consumer Protection, 2026)
This study was conducted to investigate Tobamoviruses infecting tomatoes. Leaf samples (n=10) from symptomatic tomato plants were screened for Tobamoviruses using Enzyme Linked Immune-Sorbent Assay (ELISA) and group specific antibodies. One sample scored the highest absorbance value (3.1790) was selected. Datura Stramonium was leaf inoculated with the sample selected to confirm the infection. Total ribonucleic acid (RNA) was extracted from tomato leaves and a complementary cDNA strand was synthesized. Reverse Transcription Polymerase Chain Reaction (RT-PCR) was performed using the primers TobUni1/TobUni2 targeting coat protein (CP) of the genus Tobamovirus genome.  RT-PCR products were analyzed by agarose gel electrophoresis and sequenced. Nucleotide sequences obtained were included in the National Center for Life Informatics (NCBI) database under accession numbers (PP032058 and PP032061). The detection of 2 Tobamoviruses in a single tomato plant was confirmed when DNA fragments amplified shared 98% maximum nucleotide sequence identity with Tobacco mosaic virus (TMV) and Pepper mild mottle virus (PMMoV) CP gene retrieved from NCBI. Neighbor-Joining phylogenetic tree confirmed the relatedness grouped TMV and PMMoV sequences to those from Spain (MK087763.1) and Brazil (KT923121.1), respectively, suggesting a common origin. To the best of our knowledge, this is the first report of TMV and PMMoV mixed infection on tomato in Iraq, based on molecular approach. The two Tobamovirus co-infection may be a new threat to tomato production in Iraq.